2019
DOI: 10.1007/s42452-019-0439-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear vibration of crowned gear pairs considering the effect of Hertzian contact stiffness

Abstract: This study aims to analyze the influence of lead crowning modification of teeth on the vibration behavior of a spur gear pair. Two dynamic rotational models including an uncrowned and crowned gear are examined. Hertzian mesh stiffness is computed using tooth contact analysis in quasi-static state along a complete mesh cycle of teeth mesh. The dynamic orbits of the system are observed using some useful attractors which expand our understanding about the influence of crown modification on the vibration behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In order to achieve this goal, the dynamic models are solved in "RADAU algorithm" numerically [7,20]. The accuracy of this code has been frequently confirmed in several published papers: [7,11,12,20].…”
Section: Fixedmentioning
confidence: 96%
See 1 more Smart Citation
“…In order to achieve this goal, the dynamic models are solved in "RADAU algorithm" numerically [7,20]. The accuracy of this code has been frequently confirmed in several published papers: [7,11,12,20].…”
Section: Fixedmentioning
confidence: 96%
“…Some researchers are focused on the effect of faults on the dynamic behavior of gear pairs [11][12][13]. Peng et al [14] suggested a new idea of calculating the load transmission error (LTE) by considering the effect of the bearing supports.…”
Section: Introductionmentioning
confidence: 99%
“…The LTCA could be carried out using a variety of approaches: FEM, experiments, and analytical solutions (with certain simplifications). By comparing these methods, one can conclude that: i) the experimental method requires a well-equipped laboratory, it is cost and time demanding, moreover, measurements on rotating parts are limited to non-contact surfaces; ii) analytical solutions have been generally developed for spur or helical gear pairs, however, they are not perfectly suitable or precise for gear pairs with complicated geometries, such as a spiral gear pair; iii) nonlinear FEM (including contact analysis) has become increasingly popular in recent years [3,21,22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Equation ( 6) is a nonlinear differential equation with time-varying parameters. This governing equation is solved numerically "RADAU scheme", which is an implicit scheme of the Runge-Kutta algorithm; see, e.g., [2,3,22,25,26].…”
Section: Mesh Cycle Loaded Transmission Error[µm]mentioning
confidence: 99%
“…A wide range of methods has been used to study gear pairs [2][3][4][5][6]. The nonlinear vibration of actual gear pairs, with some likely faults and conditions, has become the main issue among researchers due to vast ranges of applications of the gear systems.…”
Section: Introductionmentioning
confidence: 99%